Nuprl Lemma : cos-sin-equation-nc
∀f,g:ℝ ⟶ ℝ.
  ((∀x,y:ℝ.  ((x = y) 
⇒ (f(x) = f(y))))
  
⇒ (∀x,y:ℝ.  ((x = y) 
⇒ (g(x) = g(y))))
  
⇒ (∀x,y:ℝ.  (f(x - y) = ((f(x) * f(y)) + (g(x) * g(y)))))
  
⇒ (∃a:ℝ. f(a) ≠ f(r0))
  
⇒ (∃b:ℝ. g(-(b)) ≠ g(b))
  
⇒ ((∀x,y:ℝ.  (f(x - y) = f(y - x)))
     ∧ (∀y:ℝ. (f(-(y)) = f(y)))
     ∧ (∀y:ℝ. (g(-(y)) = -(g(y))))
     ∧ (g(r0) = r0)
     ∧ (∃d:ℝ. f(d) ≠ r0)
     ∧ (f(r0) = r1)
     ∧ (∀x:ℝ. ((f(x)^2 + g(x)^2) = r1))
     ∧ (∀x:ℝ. (|f(x)| ≤ r1))
     ∧ (∀x,y:ℝ.  ((f(x - -(y)) + f(x - y)) = (r(2) * f(x) * f(y))))
     ∧ (∀x,y:ℝ.  ((f(x + y) + f(x - y)) = (r(2) * f(x) * f(y))))))
Proof
Definitions occuring in Statement : 
rfun-ap: f(x)
, 
rneq: x ≠ y
, 
rleq: x ≤ y
, 
rabs: |x|
, 
rnexp: x^k1
, 
rsub: x - y
, 
req: x = y
, 
rmul: a * b
, 
rminus: -(x)
, 
radd: a + b
, 
int-to-real: r(n)
, 
real: ℝ
, 
all: ∀x:A. B[x]
, 
exists: ∃x:A. B[x]
, 
implies: P 
⇒ Q
, 
and: P ∧ Q
, 
function: x:A ⟶ B[x]
, 
natural_number: $n
Definitions unfolded in proof : 
true: True
, 
squash: ↓T
, 
less_than: a < b
, 
rev_implies: P 
⇐ Q
, 
rneq: x ≠ y
, 
iff: P 
⇐⇒ Q
, 
or: P ∨ Q
, 
exists: ∃x:A. B[x]
, 
less_than': less_than'(a;b)
, 
le: A ≤ B
, 
nat: ℕ
, 
guard: {T}
, 
rfun-ap: f(x)
, 
top: Top
, 
not: ¬A
, 
false: False
, 
req_int_terms: t1 ≡ t2
, 
rev_uimplies: rev_uimplies(P;Q)
, 
uimplies: b supposing a
, 
uiff: uiff(P;Q)
, 
so_apply: x[s]
, 
so_lambda: λ2x.t[x]
, 
uall: ∀[x:A]. B[x]
, 
prop: ℙ
, 
member: t ∈ T
, 
cand: A c∧ B
, 
and: P ∧ Q
, 
implies: P 
⇒ Q
, 
all: ∀x:A. B[x]
Lemmas referenced : 
radd-preserves-rleq, 
radd_comm, 
rabs-of-nonneg, 
rabs-rnexp, 
rnexp-one, 
rleq_functionality, 
rnexp2-nonneg, 
rleq-int, 
rabs_wf, 
square-rleq-implies, 
rmul-identity1, 
rmul-zero-both, 
rminus-zero, 
rless_wf, 
rless-int, 
rneq_irreflexivity, 
rneq_functionality, 
req-implies-req, 
rmul_preserves_req, 
squares-req, 
rneq-cases, 
rmul_comm, 
rnexp2, 
le_wf, 
false_wf, 
rnexp_wf, 
radd-rminus-assoc, 
radd-preserves-req, 
req_inversion, 
rmul_functionality, 
radd_functionality, 
req_transitivity, 
req_weakening, 
real_term_value_minus_lemma, 
rfun-ap_functionality, 
itermMinus_wf, 
itermConstant_wf, 
real_term_value_const_lemma, 
real_term_value_var_lemma, 
real_term_value_mul_lemma, 
real_term_value_add_lemma, 
real_term_value_sub_lemma, 
real_polynomial_null, 
req_functionality, 
req-iff-rsub-is-0, 
itermVar_wf, 
itermMultiply_wf, 
itermAdd_wf, 
itermSubtract_wf, 
rmul_wf, 
radd_wf, 
rsub_wf, 
req_wf, 
all_wf, 
int-to-real_wf, 
rminus_wf, 
rfun-ap_wf, 
rneq_wf, 
exists_wf, 
real_wf
Rules used in proof : 
equalitySymmetry, 
equalityTransitivity, 
inrFormation, 
baseClosed, 
imageMemberEquality, 
inlFormation, 
minusEquality, 
dependent_pairFormation, 
unionElimination, 
applyEquality, 
functionExtensionality, 
dependent_set_memberEquality, 
promote_hyp, 
allFunctionality, 
levelHypothesis, 
addLevel, 
independent_functionElimination, 
voidEquality, 
voidElimination, 
isect_memberEquality, 
intEquality, 
int_eqEquality, 
approximateComputation, 
dependent_functionElimination, 
independent_isectElimination, 
productElimination, 
functionEquality, 
natural_numberEquality, 
hypothesisEquality, 
lambdaEquality, 
sqequalRule, 
thin, 
isectElimination, 
sqequalHypSubstitution, 
because_Cache, 
independent_pairFormation, 
hypothesis, 
extract_by_obid, 
introduction, 
cut, 
lambdaFormation, 
sqequalReflexivity, 
computationStep, 
sqequalTransitivity, 
sqequalSubstitution
Latex:
\mforall{}f,g:\mBbbR{}  {}\mrightarrow{}  \mBbbR{}.
    ((\mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (f(x)  =  f(y))))
    {}\mRightarrow{}  (\mforall{}x,y:\mBbbR{}.    ((x  =  y)  {}\mRightarrow{}  (g(x)  =  g(y))))
    {}\mRightarrow{}  (\mforall{}x,y:\mBbbR{}.    (f(x  -  y)  =  ((f(x)  *  f(y))  +  (g(x)  *  g(y)))))
    {}\mRightarrow{}  (\mexists{}a:\mBbbR{}.  f(a)  \mneq{}  f(r0))
    {}\mRightarrow{}  (\mexists{}b:\mBbbR{}.  g(-(b))  \mneq{}  g(b))
    {}\mRightarrow{}  ((\mforall{}x,y:\mBbbR{}.    (f(x  -  y)  =  f(y  -  x)))
          \mwedge{}  (\mforall{}y:\mBbbR{}.  (f(-(y))  =  f(y)))
          \mwedge{}  (\mforall{}y:\mBbbR{}.  (g(-(y))  =  -(g(y))))
          \mwedge{}  (g(r0)  =  r0)
          \mwedge{}  (\mexists{}d:\mBbbR{}.  f(d)  \mneq{}  r0)
          \mwedge{}  (f(r0)  =  r1)
          \mwedge{}  (\mforall{}x:\mBbbR{}.  ((f(x)\^{}2  +  g(x)\^{}2)  =  r1))
          \mwedge{}  (\mforall{}x:\mBbbR{}.  (|f(x)|  \mleq{}  r1))
          \mwedge{}  (\mforall{}x,y:\mBbbR{}.    ((f(x  -  -(y))  +  f(x  -  y))  =  (r(2)  *  f(x)  *  f(y))))
          \mwedge{}  (\mforall{}x,y:\mBbbR{}.    ((f(x  +  y)  +  f(x  -  y))  =  (r(2)  *  f(x)  *  f(y))))))
Date html generated:
2018_05_22-PM-03_09_53
Last ObjectModification:
2018_05_20-PM-11_53_20
Theory : reals_2
Home
Index